A comparative investigation of the chemical reduction of graphene oxide for electrical engineering applications - Chudziak, Tomasz; Montes-García, Verónica; Czepa, W odzimierz; Pakulski, Dawid; Musia, Andrzej; Valentini, Cataldo; Bielejewski, Micha; Carlin, Michela; Tubaro, Aurelia; Pelin, Marco; Samorì, Paolo; Ciesielski, Artur (Nanoscale, 2023)
The presence of oxygen-containing functional groups on the basal plane and at the edges endows graphene oxide (GO) with an insulating nature, which makes it rather unsuitable for electronic applications. Fortunately, the reduction process makes it possible to restore the sp 2 conjugation. Among various protocols, chemical reduction is appealing because of its compatibility with large-scale production. Nevertheless, despite the vast number of reported chemical protocols, their comparative assessment has not yet been the subject of an in-depth investigation, rendering the establishment of a structure-performance relationship impossible. We report a systematic study on the chemical reduction of GO by exploring different reducing agents (hydrazine hydrate, sodium borohydride, ascorbic acid (AA), and sodium dithionite) and reaction times (2 or 12 hours) in order to boost the performance of chemically reduced GO (CrGO) in electronics and in electrochemical applications. In this work, we provide evidence that the optimal reduction conditions should vary depending on the chosen application, whether it is for electrical or electrochemical purposes. CrGO exhibiting a good electrical conductivity (>1800 S m −1 ) can be obtained by using AA (12 hours of reaction), Na 2 S 2 O 4 and N 2 H 4 (independent of the reaction time). Conversely, CrGO displaying a superior electrochemical performance (specific capacitance of 211 F g −1 , and capacitance retention >99.5% after 2000 cycles) can be obtained by using NaBH 4 (12 hours of reaction). Finally, the compatibility of the different CrGOs with wearable and flexible electronics is also demonstrated using skin irritation tests. The strategy described represents a significant advancement towards the development of environmentally friendly CrGOs with ad hoc properties for advanced applications in electronics and energy storage. Various reducing agents and reaction times are systematically investigated to enhance the performance of chemically reduced GO (CrGO) in electronics and electrochemical applications.